Efektivitas Program Kota Tanpa Kumuh (Kotaku) Dalam Menangani Permukiman Kumuh Di Kota Padang : (Studi Kasus : Kelurahan Binuang Kampung Dalam Kecamatan Pauh) - Fitria Yulia; Bambang Istijono; Benny Hidayat (Jurnal Niara, 2024)
West Sumatera Province is one of the 15 provinces with the highest slum area in Indonesia. The city of Padang, as the largest city and the provincial capital, has a number of slum areas with an area of 122.33 ha. Of the 22 Kelurahan in Padang, one of the widest slum areas is in the Kelurahan Binuang Kampung Dalam. The KOTAKU program is then present to direct and synergize all forms of collaboration between parties to prevent and improve the quality of slum settlements, especially the community as active development subjects. Within two years, the KOTAKU program initiated CFW (Cash For Work) and Sanitation Assistance activities with a total budget of nearly one billion by involving the full participation of the people there. This thesis aims to analyze how effective and the inhibiting factors of the KOTAKU Program are in dealing with slum settlements in Binuang Kampung Dalam Village. This study used a descriptive qualitative approach, and the method of selecting informants used a purposive sampling technique with the method of measuring program effectiveness using the Pentagonal Assets 7 Indicators. The results showed that the implementation of the KOTAKU program in Binuang Kampung Dalam Kelurahan focused on road repairs with a volume of 2,352.4 meters, drainage improvements with a volume of 275.7 meters, community capacity building 1 package, and sanitation improvement assistance to 100 families. However, the KOTAKU program is still considered less effective, because it does not bring changes to the other three indicators. The factors inhibiting the effectiveness of the program are the absence of programs on the indicators of building order, waste management and fire protection and the slow disbursement of funds